Bi-directional Unitary and Holographic Lorentz-Friedman Black Hole Radiation (Global Journal of Science Frontier Research, 2017)
Abstract not found
Keywords: inflationary; matter-antimatter asymmetry; Lorentz-Friedman; obsever in bi-directional